Correlates of alcohol consumption among Germans in the second half of life: results of a population-based observational study - Hajek, André; Weyerer, Siegfried (BMC geriatrics, 2017)
Several studies have investigated the predictors of alcohol consumption behavior among adolescents and young adults. However, the body of evidence about the relationship between in particular psychological factors and alcohol consumption among individuals in the second half of life is still limited. Hence, we aimed at identifying factors associated with alcohol consumption among individuals aged 40 and above, especially focusing on psychological correlates. Methods: Data were derived from a population-based sample of community-dwelling individuals aged 40 to 95 years (n = 7820) in Germany. Alcohol consumption was rated as ‘never’ (never drinkers), ‘rarer than once a month’, ‘one to three times a month’, ‘once a week’, ‘several times a week’ (occasional drinkers), and ‘daily’ (daily drinkers). Socio-economic factors, the illness level and physical activity were considered as possible determinants of alcohol consumption. In addition, positive and negative affect, life satisfaction, optimism, self-esteem, self-efficacy, and self-regulation were included as psychological factors. Multinomial regressions were used to identify factors associated with drinking behavior. Results: 12.0% of the individuals were daily drinkers, 76.5% were occasional drinkers, and 11.5% of the individuals never drank alcohol. After adjusting for various potential confounders, multinomial logistic regressions revealed that, compared with never drinking, occasional and daily drinking were positively associated with a decreased loneliness, a higher life satisfaction, a higher positive affect, a higher optimism, a higher self-efficacy (occasional drinkers), a higher self-esteem, and less perceived stress. In addition, occasional and daily drinking were positively associated with less physical illnesses, male gender, and income as compared with never drinking. Conclusions: The current study extends the existing literature on alcohol consumption behavior by new insights of correlates of drinking behavior among individuals in the second half of life. Since interventions are available to address this risk factor, this might help to identify individuals with increased alcohol consumption.